Assembling different antennas of the gp120 high mannose-type glycans on gold nanoparticles provides superior binding to the anti-HIV antibody 2G12 than the individual antennas. (20th March 2015) - Chiodo, Fabrizio; Enríquez-Navas, Pedro M.; Angulo, Jesús; Marradi, Marco; Penadés, Soledad
Graphical abstract: Highlights: Gold glyconanoparticles coated with partial structures of Man9GlcNAc2 were prepared. Oligomannoside assembly on the nanoparticles 'rebuilds' the Man9 of the HIV gp120. SPR and STD-NMR techniques give information about 2G12/glyconanoparticle interaction. The oligomannosides' co-presence on glyconanoparticles improves synergistically the binding to 2G12. Abstract: In order to re-build Man9 GlcNAc2 clusters of the HIV gp120 glycoprotein, ∼2 nm gold glyconanoparticles (GNPs) were coated with the synthetic partial structures of Man9, the tetramannoside Manα1–2Manα1–2Manα1–3Manα1– and the pentamannoside Manα1–2Manα1–3[Manα1–2Manα1–6]Manα1–. Their interactions with the anti-HIV broadly neutralizing antibody 2G12 were studied by surface plasmon resonance (SPR)-based biosensors and saturation transfer difference (STD)-NMR spectroscopy. A synergistic effect of the tetra- and pentamannosides multimerized on a same GNP was observed. The assembly of these antennas of the gp120 high-mannose type glycan on GNPs provided superior binding to the anti-HIV antibody 2G12 with respect to GNPs carrying only the individual oligomannosides. The results presented in this work provide new molecular information on the interactions between clusters of oligomannosides and 2G12 that could help in the design of a carbohydrate-based vaccine against HIV.